Cover Image. Issue 1 (17th January 2019) - Finlayson, Andrew; Phillips, Emrys; Benediktsson, Ívar Örn; Zoet, Lucas K.; Iverson, Neal R.; Everest, Jez
Abstract : The cover image is based on the Research Article Subglacial drumlins and englacial fractures at the surge‐type glacier, Múlajökull, Iceland by Andrew Finlayson et al., https://doi.org/10.1002/esp.4485 . Image Credit: Ívar Örn Benediktsson.